The Pharmacology of Anesthetic Drugs / A Syllabus for Students and Clinicians: Fifth Edition - Second Printing - Adriani John M.D.; Charles C Thomas (1973)
Preface, Effects of Physical and Chemical Properties on Pharmacological Activity, Administration and Absorption and Elimination of Anesthetic Drugs, General Systemic Effects, Administration of Volatile Drugs, Gaseous Agents, Volatile Agents, Inorganic Nonvolatile Agents, Aliphatic Nonvolatile Agents, Barbiturates and Other Nonvolatile Agents, Analgesics, Local Anesthetics, Nonanesthetic Drugs Used in Conjuction with Anesthesia, Inorganic Gases Used in Conjuction with Anesthesia, Some Clinical Considerations, Glossary, Bibliography, Drug Index, Index.